Maternal cardiovascular adaptation to twin pregnancy: a population-based prospective cohort study - Maria C. Adank; Zoe A. Broere-Brown; Romy Gonçalves; M. Kamran Ikram; Vincent W. V. Jaddoe; Eric A. P. Steegers; Sarah Schalekamp-Timmermans (BMC Pregnancy and Childbirth, 2020)
Abstract Background In women with singleton pregnancies, maternal adaptation is considered a stress test for later life cardiovascular disease. The aim of this study was to assess maternal adaptation in women with twin pregnancies compared to women carrying singletons during and after pregnancy. Methods This was a population based prospective cohort study of 91 women with twin pregnancies and 8107 women carrying singletons. The association of twin pregnancy and maternal adaptation was examined using regression analyses. In pregnancy, we measured soluble fms-like tyrosine kinase-1 (sFLT-1), placental growth (PGF) factor, systolic (SBP) and diastolic blood pressure (DBP), and the occurrence of pre-eclampsia (PE). After pregnancy, measurements were obtained on SBP and DBP, cardiac function, retinal calibres, intima media thickness and distensibility of the common carotid artery. Results sFLT-1 and PGF concentrations were higher in early (13.4 weeks) and mid-pregnancy (20.4 weeks) in women with twin pregnancies compared to women with singleton pregnancies. Women with twin pregnancies had a different DBP pattern in pregnancy. Women with twin pregnancies were more likely to have PE (odds ratio 3.63; 95% CI [1.76 to 7.48]). Six and ten years after pregnancy, no differences in maternal adaptation were observed. Conclusions Women with twin pregnancies show an altered adaptation during pregnancy compared to women with singleton pregnancies. This is associated with a substantially increased incidence of PE, but does not lead to persistent altered maternal adaptation years after pregnancy.